2019
DOI: 10.18502/kls.v4i13.5265
|View full text |Cite
|
Sign up to set email alerts
|

Husban Behavior in Pregnancy-Postpartum Care and Wife’s Reproductive Health

Abstract: Background:In the process pregnancy-postpartum, the role of the husband is very important and necessary. It is highly expected for the husbands to accompany their wives, so that their wives can have healthy pregnancy which is later able to give birth a healthy baby and the mothers can survive. Objectives: The purpose of this study is to find out the effect of husband's knowledge regarding Antenatal Care (ANC) and Early High-Risk Detection, husband behavior in the pregnancy-postpartum care with reproductive hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Regarding the support provided by the husbands, this current study found that pregnancy is something that husbands really look forward to and they are willing to help their pregnant wives, such as providing nutritious food to help fulfill the needed vitamins. It is also supported by a previous study conducted by Nur et al (2019) who found that the husband supports his wife's pregnancy by accompanying her to the ANC service, reminding the wife to take iron tablets, and finding out information related to his wife's pregnancy [25]. These kinds of support are essential because a husband's participation in the wife's pregnancy is believed to be an important step to improve maternal health status [26].…”
Section: Discussionmentioning
confidence: 72%
“…Regarding the support provided by the husbands, this current study found that pregnancy is something that husbands really look forward to and they are willing to help their pregnant wives, such as providing nutritious food to help fulfill the needed vitamins. It is also supported by a previous study conducted by Nur et al (2019) who found that the husband supports his wife's pregnancy by accompanying her to the ANC service, reminding the wife to take iron tablets, and finding out information related to his wife's pregnancy [25]. These kinds of support are essential because a husband's participation in the wife's pregnancy is believed to be an important step to improve maternal health status [26].…”
Section: Discussionmentioning
confidence: 72%
“…Penelitian yang dilakukan Nur et al, menunjukkan perbedaan signifikan kejadian masalah kesehatan reproduksi yang dialami oleh istri antara suami dengan tingkat pendidikan rendah dan tingkat pendidikan tinggi. 17 Pendidikan berorientasi terhadap wawasan dan pengetahuan yang berimplikasi pada pengambilan keputusan. Semakin rendah tingkat pengetahuan suami, maka semakin sedikit atau terbatas akses yang dimiliki terhadap informasi kesehatan yang menyebabkan kesulitan dalam mengambil keputusan yang efektif.…”
Section: Pembahasanunclassified
“…Research by Nur et al, 2019 shows that the husband's knowledge of early detection of childbirth affects maternal reproductive health. It is hoped that the development of models to improve communication, information and education to husbands can be a preventive effort in improving women's reproductive health.…”
Section: Informational Supportmentioning
confidence: 99%